(cRGD)2 peptides modified nanoparticles increase tumor-targeting therapeutic effects by co-delivery of albendazole and iodine-131. Issue 1 (January 2022) - Liu, Shengli; Liu, Honglian; Sun, Hao; Deng, Shengming; Yue, Ling; Weng, Zhen; Yang, Jianfeng; Zuo, Bin; He, Yang; Zhang, Bin
Abstract : Albendazole (ABZ), a clinical antiparasitic drug, has shown potential antitumor effects in various tumors. Herein, we prepared dimeric cRGD [(cRGD)2 ] modified human serum albumin (HSA) nanosystem to co-delivery of albendazole (ABZ) and iodine-131 ( 131 I) for chemoradiotherapy of triple-negative breast cancer (TNBC). HSA@ABZ NPs were synthesized by the self-assembly method. 131 I-(cRGD)2 /HSA@ABZ NPs were fabricated through covalently binding HSA@ABZ NPs with (cRGD)2 peptides, followed by chloramine T direct labeling with 131 I. In vitro therapeutic effects on TNBC (MDA-MB-231 and 4T1 cells) were determined using MTT assay, crystal violet assay, wound-healing assay and western blotting analysis. In vivo treatment was performed using 4T1-bearing mice, and the tumor-targeting efficacy was assessed by gamma imaging. The distribution of NPs was quantitatively analyzed by detecting the gamma counts in tumor and main organs. The nanoparticles possessed negative charge, moderate size and good polydispersity index. Dual responding to pH and redox, the in vitro release rate of ABZ was more than 80% in 72 h. In vitro, NPs inhibited the proliferation of TNBC cells in a concentration-dependent manner and decreased cell migration. Western blotting analysis showed that the NPs, as well as free ABZ, cell-dependently induced autophagy and apoptosis by restraining or promoting the expression of p-p38 and p-JNK MAPK. In vivo, gamma imaging exhibited an earlier and denser radioactivity accumulation in tumor of 131 I-(cRGD)2 /HSA@ABZ NPs compared to NPs free of (cRGD)2 conjugating. Furthermore, 131 I-(cRGD)2 /HSA@ABZ NPs significantly suppressed tumor growth by restraining proliferation and promoting apoptosis in vivo. Our study suggested that the nanoparticles we developed enhanced tumor-targeting of ABZ and increased antitumor effects by combination of chemotherapy and radiotherapy.